Ouvidoria pública como instrumento de mudança - Antonio Semeraro Rito Cardoso (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– The present work points out to show the Public Ombudsman Service as a changing, inclusion and social control tool. As methodology, a bibliography revision was made, besides the author experience in ombudsman service management, showing how the Public Ombudsman Service contributes in building those tasks through the direct and active citizen participation, which represents, a privileged locus to the participative democracy exercise, citizenship achievement and social control of everything that is public. Also, through the ethics valorization, which helps in the civil society renewing, based on the trust and respect rebuilding, which depends on the Public Ombudsman Office`s autonomy and efficiency. Therefore, the conclusion is that, in order to have the Public Ombudsman Service doing, in their plenitude, their part of changing inductor, it is necessary that exists ethics valorization; suitable public ombudsman skills and profile; Public Ombudsman Services search for effectiveness and autonomy.
Keywords: H11; H19; J52; M14; 330